hydrochemical analysis and evaluation of groundwater quality of an alluvial aquifer. algeria - Drias, Tarek; Fehdi, Chemseddine; Belloula, Moufida (Euro-Mediterranean Conference for Environmental Integration, 2017)
The study of the water quality in the shallow aquifer of Tebessa-Morsott was carried out to perform a preliminary assessment of the hydrochemical quality of same groundwater samples and their suitability for irrigation uses. The high salinity coupled with groundwater level decline pose serious problems for current irrigation and domestic water supplies as well as for future exploitation. The statistical treatment of hydrochemical data by principal component analysis revealed two components related to salinity and pollution. The US salinity diagram illustrates that most of the groundwater samples fall in C3S1- C4S1 quality with high salinity hazard and low sodium hazard.